Perkuliahan Ekologi dengan Diktat pada Mahasiswa Pendidikan Geografi FKIP Universitas PGRI Palangka Raya - Norsandi, Dedy (Anterior Jurnal, 2018)
The purpose of this study are to knowing the teaching with dictat and the difficulties of it, properness of ecology dictat according to lectures and the opinion of college as a user, the result of study of college after using the dictat. To reach that purpose, the dictat tried to college and evaluation from lectures. The sample of this study are class A of 2012 colleger at first semester 2013/2014 who are programming ecology subjeck in geography education couses. Data was got by enquette and observation and than analysed by quantity description with distributed frequenty and table presentation.The result of this study are the ecology dictat properly for teaching according to colleger, reviewer and lectures with the value is 4,1 (good category), and the study result of college on the average of 70,00 (good category), the opinion of collegers they feel happy using dictat as one of literature in their study. But there are some opinion that the dictat must be added with pictures and illustration to completing abstract material before publishing.